Productive and reproductive parameters of local breeds of livestock and poultry of Sri Lanka - Chandrasiri, A.D.N. (1991)
The work is a country paper on productive and reproductive performance of animal genetic resource of Sri Lanka presented on the meeting of counterpart scientists of SAARC (South Asian Association for Regional Co-operation) member countries on Animal genetic resource conservation. The paper includes information on population, some physical descriptions and productive and reproductive performance of native cattle, buffaloes, sheep, goats, pigs and chicken. Native chicken population represents only about 20% of the total poultry population. They have metallic brown, brick red, golden and metallic blue plumage colours predominantly. Egg weight, hen day production and clutch size (size of batch of eggs) are 48 g, 30% and 20 eggs, respectively.